2020
DOI: 10.1167/tvst.9.9.8
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomography Is More Sensitive for Hydroxychloroquine-Related Structural Abnormalities Than Short-Wavelength and Near-Infrared Autofluorescence

Abstract: Spectral-domain optical coherence tomography is more sensitive for hydroxychloroquine-related structural abnormalities than short-wavelength and near-infrared autofluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(55 reference statements)
0
2
0
1
Order By: Relevance
“…Jauregui et al similarly reported in a study of 30 patients that SD-OCT was more sensitive in detecting HCQ retinopathy compared with SW-AF and near-infrared autofluorescence (NIR-AF) [58]. They described 10 patients who presented with early changes in the outer retinal layers (EZ attenuation and/or IZ continuity loss) in SD-OCT scans, yet with qualitatively normal SW-AF and NIR-AF scans [58]. Conversely, four patients presented with bull's-eye maculopathy in SW-AF and NIR-AF scans with corresponding parafoveal outer retina disruption on SD-OCT scans [58].…”
Section: Comparison Of Oct and Fafmentioning
confidence: 99%
See 1 more Smart Citation
“…Jauregui et al similarly reported in a study of 30 patients that SD-OCT was more sensitive in detecting HCQ retinopathy compared with SW-AF and near-infrared autofluorescence (NIR-AF) [58]. They described 10 patients who presented with early changes in the outer retinal layers (EZ attenuation and/or IZ continuity loss) in SD-OCT scans, yet with qualitatively normal SW-AF and NIR-AF scans [58]. Conversely, four patients presented with bull's-eye maculopathy in SW-AF and NIR-AF scans with corresponding parafoveal outer retina disruption on SD-OCT scans [58].…”
Section: Comparison Of Oct and Fafmentioning
confidence: 99%
“…They described 10 patients who presented with early changes in the outer retinal layers (EZ attenuation and/or IZ continuity loss) in SD-OCT scans, yet with qualitatively normal SW-AF and NIR-AF scans [58]. Conversely, four patients presented with bull's-eye maculopathy in SW-AF and NIR-AF scans with corresponding parafoveal outer retina disruption on SD-OCT scans [58]. There were no patients with SW-AF or NIR-AF abnormalities who had normal SD-OCT scans [58].…”
Section: Comparison Of Oct and Fafmentioning
confidence: 99%
“…Als mögliche Screening-Verfahren stehen hochauflösende Perimetrie, multifokales ERG (mfERG), OCT, NIA und FAF zur Verfügung. Dabei ist die Diskussion, ob eines dieser Verfahren überlegen ist, offen, da die Studien Patienten mit unterschiedlicher Therapiedauer, ohne und mit Retinopathien, oder Retinopathien unterschiedlicher Stadien einschlossen und nur selten alle Untersuchungstechniken eingesetzt wurden 30 , 31 . Darüber hinaus sind mehrere Einzelfälle beschrieben, die nur in jeweils einem diagnostischen Verfahren Veränderungen zeigen.…”
Section: Klinische Anwendungen Und Einsatzmöglichkeitenunclassified
“…[204] Prolonged FLIO lifetimes have been noted in a parafoveal distribution corresponding to regions of toxicity. [205] Despite this, HD-OCT has been reported as more sensitive for detecting HCQ-related structural damage than either SW-AF or NIR-AF, [206] and current guidelines still recommend HD-OCT and VF as primary screening modalities.…”
Section: Hydroxychloroquine (Hcq)mentioning
confidence: 99%